POLITICAL CONFLICT IN LAUT BERCERITA BY LEILA S. CHUDORI: INSIGHTS FROM NEW HISTORICISM - Hartati, Rita; Pratiwy, Devi; Anayati, Wan (JOURNAL OF LANGUAGE, 2024)
This research investigates the political conflict depicted in Leila S. Chudori's novel Laut Bercerita, focusing on the portrayal of the student’s movement and authoritarian regime dominated by military force in Indonesia during the New Order era. Drawing on the theories of Sociology of Literature and New Historicism, the study aims to analyze the socio-political dynamics embedded within the narrative. The qualitative descriptive method is employed to examine the text in-depth, considering its historical significance and literary merits. Through close textual analysis, the research reveals the intricate interplay between fiction and reality, shedding light on the experiences of activists and the repressive tactics of the regime. The novel vividly captures the determination, struggles, and sacrifices of student activists as they challenge authoritarian rule, providing valuable insights into Indonesia's socio-political landscape. Additionally, the study explores the ways in which literature serves as a vehicle for social critique and historical remembrance, emphasizing the enduring relevance of Chudori's work in contemporary discourse. This research contributes to a deeper understanding of Indonesian history and literature, underscoring the importance of literature as a tool for socio-political commentary and cultural preservation.